Freestyle Critical Appraisal (Quantitative Study) - Sowtali, Siti Noorkhairina; Rodzlan Hasani, Wan Shakira (2021)
This critical appraisal is an output from the authors' experiences throughout her PHD journey, involved in teaching and research consultation. This critical appraisal had been used particularly in screening and finalizing relevant journals for writing literature reviews.